2014
DOI: 10.1111/plb.12205
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in sunflower leaf and cell growth under high salinity

Abstract: A group of sunflower lines that exhibit a range of leaf Na(+) concentrations under high salinity was used to explore whether the responses to the osmotic and ionic components of salinity can be distinguished in leaf expansion kinetics analysis. It was expected that at the initial stages of the salt treatment, leaf expansion kinetics changes would be dominated by responses to the osmotic component of salinity, and that later on, ion inclusion would impose further kinetics changes. It was also expected that diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…6), it is conceivable that the reduction of leaf area and shoot fresh weight at this stage was mainly caused by the reduction of cell elongation and division (osmotic phase of stress adaptation) (Munns and Tester, 2008). In a study comparing sunflower lines with different ability in ion transport and compartmentation (Céccoli et al, 2015), it was shown that early stage accumulators (see 100 mM NaCl stressed GEN plants at 13 DAST, Fig. 6) presented impaired cell division, which resulted in leaves with reduced cell number than in a Na + -excluding line.…”
Section: Cultivarmentioning
confidence: 98%
“…6), it is conceivable that the reduction of leaf area and shoot fresh weight at this stage was mainly caused by the reduction of cell elongation and division (osmotic phase of stress adaptation) (Munns and Tester, 2008). In a study comparing sunflower lines with different ability in ion transport and compartmentation (Céccoli et al, 2015), it was shown that early stage accumulators (see 100 mM NaCl stressed GEN plants at 13 DAST, Fig. 6) presented impaired cell division, which resulted in leaves with reduced cell number than in a Na + -excluding line.…”
Section: Cultivarmentioning
confidence: 98%
“…Compared to other crop species, cultivated sunflower has been shown to be moderately salt tolerant (Katerji, van Hoorn, Hamdy, & Mastrorilli, ), as has safflower, a closely related crop species (Yeilaghi, Arzani, & Ghaderian, ). Additionally, cultivated sunflower shows genotypic variation in response to abiotic stresses, including drought (e.g., Ahmad, Ahmad, Ashraf, Ashraf, Waraich, ), nutrients (e.g., Cechin & de Fatimas Fumis, ) and salinity (e.g., Ceccoli et al, ; Katerji et al, ; Rawson & Munns, ; Shi & Sheng, ). Given the moderate salt tolerance and putative genotypic variation in response to salinity in sunflower, there is a potential for identifying a range of salinity tolerances in cultivated sunflower genotypes that could be linked to physiological mechanisms underlying salt tolerance given a broad set of genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic response to salinity was found to affect leaves by increasing respiration and reducing leaf area and limiting cell division, which generally limit growth, e.g., Refs. [ 44 , 45 ], but may also result in more leaves [ 46 ]. Together, the results further support the conclusion that A. hierochuntica relies on plastic responses in relation to harsh conditions.…”
Section: Discussionmentioning
confidence: 99%